Comparative Assessment of Lower Urinary Tract Infections in Hospitalized Adults from Western Romania: A Retrospective Cohort with Microbiological Analysis - Adela Benea; Mirela Turaiche; Ovidiu Rosca; Elena Hogea; Madalina-Ianca Suba; Norberth-Istvan Varga; Uday Shree Akkala Shetty; Daniel Porav-Hodade; Ileana Enatescu; Adrian Cosmin Ilie; Ciprian Rachieru; Daniel-Florin Lighezan; et al. (Microorganisms)
Urinary tract infections (UTIs) remain a leading cause of healthcare-associated morbidity, particularly in patients with indwelling urinary catheters. This study aimed to compare catheter-associated (CAUTIs) and non-catheter-associated UTIs of the lower tract among hospitalized adults in Western Romania, identify potential predictors of prolonged hospital stay, and explore the interplay of inflammatory markers and clinical outcomes. We retrospectively examined 130 patients diagnosed with UTIs from 2020 to 2024. Demographic data, comorbidities, laboratory parameters (CRP, procalcitonin, fibrinogen, white blood cell counts), and microbiology results were assessed. Patients were divided into CAUTI (n = 72) and non-catheter UTI (n = 58) groups. CAUTI patients had a significantly longer mean hospital stay (13.9 ± 4.3 vs. 11.7 ± 3.8 days, p = 0.01). E. coli (29.2%), Klebsiella pneumoniae (18.5%), and mixed flora (11.5%) predominated overall, with Pseudomonas aeruginosa trending higher in CAUTIs (15.3% vs. 5.2%). Diabetic status correlated with higher CRP (54.7 ± 18.2 vs. 46.9 ± 15.7 mg/dL, p = 0.04) and increased intensive care unit (ICU) admission (23.5% vs. 9.4%, p = 0.03). In a subgroup of 65 patients, CRP demonstrated a moderate positive correlation with length of stay (r = 0.47, p = 0.02). Logistic regression indicated that CAUTI was associated with 2.3-fold higher odds of extended hospitalization (95% CI: 1.2–4.4, p = 0.02), adjusting for age, diabetes, and CRP levels. CAUTIs are linked to more resistant pathogens, longer hospitalizations, and potentially greater clinical complications. Diabetes further compounds risk, as reflected in higher inflammatory markers and ICU admissions.